2021
DOI: 10.1186/s12302-021-00533-8
|View full text |Cite
|
Sign up to set email alerts
|

Dead in the water: comment on “Development of an aquatic exposure assessment model for imidacloprid in sewage treatment plant discharges arising from use of veterinary medicinal products”

Abstract: Anthe et al. (Environ Sci Eur 32:147, 2020. 10.1186/s12302-020-00424-4) develop a mathematical model to calculate the contribution of veterinary medicinal products (VMPs) to the levels of imidacloprid observed in the UK water monitoring programme. They find that VMPs make only a very small contribution to measured pollution levels, and that the estimated concentrations do not exceed ecotoxicological thresholds. However, shortcomings in methodology—including the implicit assumption that imidacloprid applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The second-largest threat to the aquatic ecosystems after wastewater discharge is reducing the dissolved oxygen content caused by the oxygen intake by organic matter. All of the changes mentioned above were identified as hazardous due to their accelerating effects on the eutrophication process, causing a further imbalance to the entire ecosystem [ 30 ]. However, in most cases, the long-distance sampling is not performed and the changes in those parameters on a distant stretch of rivers remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The second-largest threat to the aquatic ecosystems after wastewater discharge is reducing the dissolved oxygen content caused by the oxygen intake by organic matter. All of the changes mentioned above were identified as hazardous due to their accelerating effects on the eutrophication process, causing a further imbalance to the entire ecosystem [ 30 ]. However, in most cases, the long-distance sampling is not performed and the changes in those parameters on a distant stretch of rivers remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Perkins et al dismiss, without any validation, other potential sources of imidacloprid found in UK rivers [2]. We believe that most of the arguments in the Perkins et al commentary relates to exposure pathways without a consideration of their plausibility, relevance or significance.…”
Section: Commentsmentioning
confidence: 86%
“…Perkins et al [2] seem to question the validity of the well-established biocide modelling approach that is set out by the Authorities responsible for regulating biocides in the EU (such as the use of default values) [3]. The model is based on the principles of the environmental risk assessment for Biocidal Products, which provide protection over an extended period (e.g.…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic matter, often forming a facultative anaerobic environment. Here, bacteria are permanently present, have poor adhesion to the material, and are easily released [14][15].…”
Section: The Principle Of Biological Aerated Filter To Purify Organic...mentioning
confidence: 99%